Long-term impact of sarcopenia on functional decline and mortality in community-dwelling older adults: a systematic review and meta-analysis - Zhao, Yuan; Jiang, Yueying; Guo, Yunyu; Pan, Wanya; Tian, Wenhao; Tang, Leiwen; Feng, Xiuqin (Frontiers in Nutrition, 2026)
BackgroundSarcopenia is an age-related syndrome characterized by progressive loss of muscle mass and function. While it is considered a key predictor of adverse health outcomes, comprehensive evidence regarding its long-term impact on functional decline and mortality in community-dwelling older adults remains limited.ObjectiveTo evaluate the longitudinal association between baseline sarcopenia and risks of functional decline and all-cause mortality among community-dwelling older adults, with subgroup analyses based on methods of sarcopenia assessment and domains of functional decline.MethodsWe conducted a systematic review and meta-analysis following PRISMA 2020 and MOOSE guidelines. Seven databases were searched from inception to September 30th, 2025. We included cohort studies of older adults aged 60 years and above, with sarcopenia defined by recognized criteria, and reporting effect estimates for functional decline or mortality with follow-up for 1 year or longer. A meta-analysis based on heterogeneity was conducted using either common or random-effects models.ResultsA total of 39 studies involving 76151 participants were included. Sarcopenia was significantly associated with an increased risk of all-cause mortality (29 publications, OR = 1.79, 95%CI: 1.55~2.06) and functional decline (16 publications, OR = 1.90, 95%CI: 1.55~2.32). Subgroup analyses revealed consistent associations across different muscle mass assessment methods (DXA, BIA, and CT). Notably, sarcopenia was associated with both physical (OR = 1.91, 95%CI: 1.52~2.40) and cognitive/psychological functional decline (OR = 2.03, 95%CI: 1.35~3.05). Heterogeneity was moderate to high but did not substantially alter the results in sensitivity analyses.ConclusionThis meta-analysis confirms that sarcopenia significantly predicts long-term functional decline and mortality in community-dwelling older adults, with robust associations across multiple muscle mass measurement methods and functional domains. These findings highlight the importance of standardized sarcopenia screening and early intervention to mitigate long-term functional impairment and mortality risk in aging populations.Clinical trial registrationPROSPERO (ID CRD42024595362).